Influence of slip parameter, viscous dissipationand joule heating effect on boundary layer flow and heat transfer over a power-law stretching wedge-shaped surface with the correlation coefficient and multiple regressions - Ali, Mohammad; Alim, Abdul MD (Zielona Góra: Uniwersytet Zielonogórski)
The influence of slip parameter, viscous dissipation, and Joule heating parameter on MHD boundary layer nanofluid flow over a permeable wedge-shaped surface was analysed. The PDEs and the associated boundary conditions were transformed to a set of non-similar ODEs and the obtained system of equations was solved numerically with the help of the spectral quasi-linearization method (SQLM) by applying suitable software.
Keywords: boundary layer; wedge angle; stretching surface; permeability; slip condition